PHYTOCHEMICAL ANALYSIS AND ANTIOXIDANT POTENTIAL OF EXTRACTS ETHANOL MACROALGAE Padina australis FROM TEGAL MAS ISLAND LAMPUNG - Fatimah Alhafizoh; Endang Linirin Widiastuti; Nuning Nurcahyani; Ni Luh Gede Ratna Juliasih; Endah Setyaningrum (Analit : Analytical and Environmental Chemistry, 2024)
In the seas of Lampung, a kind of brown macroalgae known as Padina australis is commonly seen.. Padina australis is widely used in the food industry as a gelling agent, emulsifier, thickener, stabilizer and also in the medical industry. The content of phytochemical compounds that can be developed as phytopharmaceutical agents is one of them as antioxidants. The aim of this study was to analyze the phytochemical content and potential antioxidant activity of the macroalgae Padina australis. The method used was extraction by maceration in 70% ethanol as a solvent. The phytochemical test was performed qualitatively by a color reagent test. The FTIR test was performed to analyze the functional groups of the active ingredients, while the antioxidant test used the DPPH (1,1-diphenyl-2-picrylhydrazil) method. The results obtained show that the ethanol extract of Padina australis contains chemical compounds such as saponins, steroids, tannins, alkaloids, and flavonoids. Padina australis extract shows its potential as an alternative source of natural antioxidant compounds because it is able to reduce free radicals with an IC50 value of 407.96 ppm, which is classified as very weak antioxidant activity. Further research needs to be done to obtain other concentration doses so as to get the best antioxidant activity results that can be developed clinically for health products.